The Effect of Business Level Differentiation, Integrated Level Strategy and Corporate Level Strategy on Competitive Advantage is Mediated by Internal Innovation at Indonesian Army Hospitals - Akbar Akbar; Bahtiar Usman; Sarfilianty Anggiani (Syntax Corporation Indonesia, 2025)
This study aims to analyze the influence of business level differentiation strategies (Business Level Strategy Differentiation), Integrated Level Strategy (Integrated Level Strategy), and Corporate Level Strategy (Corporate Level Strategy) on Competitive Advantage in military hospitals. In addition, this study also explores the role of internal innovation as a mediating variable in the relationship between business strategy and competitive advantage. Taking into account the unique challenges faced by TNI AD hospitals, this research contributes to understanding how business strategies can increase competitiveness through internal innovation. This research was carried out quantitatively using a sampling method using the total sampling technique, where the number of samples used was 162 leaders of TNI AD class C hospitals. Data processing was carried out using the Structural Equation Modeling (SEM) method with SmartPLS Ver 4 software to analyze the relationship between exogenous and endogenous variables and test the mediating role of internal innovation in the model. The results of the study show that from several hypotheses tested, business level strategies (Business Level Differentiation) do not have a direct influence on competitive advantage or internal innovation. However, the Integrated Level Strategy and the Corporate Level Strategy have a positive effect on competitive advantage and internal innovation. In addition, internal innovation has been shown to mediate the influence of integration-level strategies on competitive advantage, but it does not mediate the relationship between business-level strategies and corporate-level strategies on competitive advantage. The theoretical implications of this study confirm that an integrated organization-level strategy can improve competitiveness through operational efficiency and innovation. Managerially, these findings indicate that military hospitals need to strengthen their culture of innovation and optimize integration strategies so that internal innovation can contribute more significantly to competitive advantage. The limitation of this study lies in the scope of the sample that only involves TNI AD class C hospitals, so the results cannot necessarily be generalized to hospitals with different levels or ownership. This research has a novelty in applying the concept of corporate strategy in the context of non-profit public service organizations, especially military hospitals. The study also combines three types of business strategies in one integrative model, providing a holistic perspective on how different strategies can complement each other in improving hospital competitiveness.